The Effect of Personality Traits, Class Level, and Gender on EFL Learners' Online Learning Acceptance among Tunisian University Students - Amani Bouzayenne (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2023)
The outbreak of the COVID-19 pandemic necessitated the transition from in-person instruction to online education. Most students in Tunisia repudiated such sudden transfer. This study, then, probes into factors that impact the online learning experience during the pandemic. Hence, it investigates the effect of affective variables, namely personality traits, on learners' acceptance of online learning in the Tunisian English as a Foreign Language (EFL) formal university context. Additionally, it scrutinizes the relationship between remote learning on the one hand and class level and gender on the other hand. The considered variables are gauged using a Likert-scale response format questionnaire. The subjects are 150 Tunisian EFL university students at the Higher Institute of Applied Studies in Humanities of Gafsa. The data analysis procedures used are the alpha internal consistency coefficient informing about the instrument's reliability and the Spearman Rho correlation, giving insight into the correlations among the study variables. The study found that personality represents a good predictor of learners' acceptance of distance learning. Regarding the class level, no significant correlation was found between this variable and acceptance of online learning. The same insignificant correlation was detected between gender and Internet-based learning. Hence, the study concludes that considering learners' differences is primordial in accounting for the success of EFL online courses.